Concussions in Community-Level Rugby: Risk, Knowledge, and Attitudes. (July 2017) - Martin, R. Kyle; Hrubeniuk, Travis J.; Witiw, Christopher D.; MacDonald, Peter; Leiter, Jeff
Background: Rugby is a popular collision sport where participants are at risk of sustaining concussions. Most research focuses on elite-level or youth divisions. Comparatively, little is known about adult community rugby. The aim of this research was to estimate the risk of sustaining a concussion during participation in community-level rugby and summarize the collective knowledge and attitudes toward concussions. Hypothesis: Concussion symptoms will be reported frequently among community-level rugby players and a substantial proportion will report a willingness to continue participation despite the risk. Study Design: Cross-sectional analysis. Level of Evidence: Level 3. Methods: An anonymous, voluntary survey was administered to all 464 senior rugby players registered in the province of Manitoba in 2015. Two primary domains were assessed: (1) concussion history from the preceding season including occurrence, symptomatology, and impact on daily activities and (2) knowledge and attitudes toward concussion risks and management. Results: In total, 284 (61.2%) rugby players responded. Concussive symptoms were reported by 106 (37.3%). Of those, 87% were formally diagnosed with a concussion and 27% missed school and/or work as a result. The danger of playing while symptomatic was recognized by 93.7% of participants, yet 29% indicated they would continue while symptomatic. Furthermore, 39% felt they were letting others down if they stopped playing due to a concussion. Conclusion: Concussive symptoms were common among the study cohort and had a notable impact on daily activities. A high proportion of players were willing to continue while experiencing symptoms despite recognizing the danger. The observed discord between knowledge and attitudes implicates a culture of "playing injured." Clinical Relevance: Understanding the risk of injury may affect an individual's decision to participate in community-level rugby. Moreover, evidence of discord between the knowledge and attitudes of players may direct future research initiatives and league governance.